Problematika Hukum Tanah Absentee serta Dampak Pengecualian bagi Aparatur Sipil Negara terhadap Ketimpangan Agraria - Nawang Wahyu Wulandari; Muhammad Rizqi; Mitha Merlyan; Prawiradijaya Prawiradijaya (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The main objective of agrarian reform in Indonesia is to achieve social welfare through equitable land distribution. This effort is mandated by Article 10 Paragraph (1) of Law No. 5 of 1960 (UUPA), which requires owners to actively cultivate agricultural land, and is reinforced by the prohibition of Absentee land ownership in Government Regulation No. 224 of 1961. However, the implementation of this policy has been ambivalent due to the exemption for civil servants through Government Regulation No. 4 of 1977. This study aims to analyze how this exemption has implications for agrarian inequality and how it relates to land conflicts in Indonesia. Using normative juridical methods and a legislative approach as well as case studies of court decisions, the results of this study show that the exemption for civil servants has created a new class of landlords that exacerbates structural inequality in land ownership. Based on data on agrarian conflicts, this exemption is often abused, which hinders land redistribution to small farmers. In terms of distributive justice theory, this policy is considered disproportionate because it prioritizes the economic security of state officials over the land sovereignty of local communities. This study recommends the need to revise Government Regulation No. 4 of 1977 and strengthen the digital land registration monitoring system to ensure that the social function of land is maintained and to close legal loopholes that perpetuate inequality.